Revolts and political violence in early modern imagery - Griesse, Malte; Barget, Monika; Boer, David de 1990- (Brill's studies on art, art history, and intellectual history, 2021)
The first in-depth analysis of how early modern people produced and consumed images of revolts and political violence, drawing on evidence from Russia, China, Hungary, Portugal, Germany, North America and other regions.